Characterization of B cells in healthy pregnant women from late pregnancy to post-partum: a prospective observational study - Lima, J (2016)
Abstract BACKGROUND: B cells play a role in pregnancy due to their humoral and regulatory activities. To our knowledge, different maturational stages (from transitional to memory) of circulating B cell subsets have not yet been characterized (cell quantification and phenotype identification) in healthy pregnant women. Thus, the objective of our study was to characterize these subsets (as well as regulatory B cells) from late pregnancy to post-partum and to compare them with the circulating B cells of non-pregnant women. METHODS: In all of the enrolled women, flow cytometry was used to characterize the circulating B cell subsets according to the expression of IgD and CD38 (Bm1-Bm5 classification system). Regulatory B cells were characterized based on the expression of surface antigens (CD24, CD27, and CD38) and the production of IL-10 after lipopolysaccharide stimulation. RESULTS: Compared to the absolute counts of B cells in the non-pregnant women (n = 35), those in the pregnant women (n = 43) were significantly lower (p < 0.05) during the 3rd trimester of pregnancy and on delivery day (immediately after delivery). The percentages of these cells on delivery day and at post-partum were significantly lower than those in the non-pregnant women. In general, the absolute counts and percentages of the majority of the B cell subsets were significantly lower in the 3rd trimester of pregnancy and on delivery day than in the non-pregnant women. However, these counts and percentages did not differ significantly between the post-partum and the non-pregnant women. The most notable exceptions to the above were the percentages of naïve B cells (which were significantly higher in the 3rd trimester and on delivery day than in the non-pregnant women) and of CD24(hi)CD38(hi) regulatory B cells (which were significantly higher in the post-partum than in the non-pregnant women). CONCLUSION: According to our study, the peripheral B cell compartment undergoes quantitative changes during normal late pregnancy and post-partum. Such findings may allow us to better understand immunomodulation during human pregnancy and provide evidence that could aid in the development of new strategies to diagnose and treat pregnancy-associated disturbances. Our findings could also be useful for studies of the mechanisms of maternal responses to vaccination and infection.